2006
DOI: 10.1128/jb.01845-05
|View full text |Cite
|
Sign up to set email alerts
|

Functional Analysis of Glucan Binding Protein B from Streptococcus mutans

Abstract: Mutans streptococci are major etiological agents of dental caries, and several of their secreted products contribute to bacterial accumulation on teeth. Of these, Streptococcus mutans glucan binding protein B (GbpB) is a novel, immunologically dominant protein. Its biological function is unclear, although GbpB shares homology with a putative peptidoglycan hydrolase from S. agalactiae and S. pneumoniae, indicative of a role in murein biosynthesis. To determine the cellular function of GbpB, we used several appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
69
1
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(73 citation statements)
references
References 51 publications
(56 reference statements)
1
69
1
2
Order By: Relevance
“…Changes in the pH of the growth medium are known to induce complex regulatory networks, as well as differential expression of multiple genes, including those involved with metabolism of sugars (26). It was previously shown that expression of gbpB, which encodes glucan-binding protein B, is altered under low-pH conditions (29). Expression of gbpC was reduced at low pH, comparable to gbpB expression in strain UA159.…”
Section: Vol 189 2007 Gbpc Expression In S Mutans 6527mentioning
confidence: 74%
“…Changes in the pH of the growth medium are known to induce complex regulatory networks, as well as differential expression of multiple genes, including those involved with metabolism of sugars (26). It was previously shown that expression of gbpB, which encodes glucan-binding protein B, is altered under low-pH conditions (29). Expression of gbpC was reduced at low pH, comparable to gbpB expression in strain UA159.…”
Section: Vol 189 2007 Gbpc Expression In S Mutans 6527mentioning
confidence: 74%
“…Monocistronic expression was previously reported for gbpB Smu , which is the pcsB homologue in S. mutans (37). Recently, it was proposed that GbpB Smu is not a cell division protein at all but rather coordinates exopolysaccharide biofilm formation with cell growth and surface biogenesis (14).…”
Section: Discussionmentioning
confidence: 99%
“…The first is that AtlA can directly mediate intercellular adhesion. Notably, the glucan binding protein B (GbpB) of S. mutans was reported to share homology with a putative peptidoglycan hydrolase from group B streptococcus (14,49,50). The possession of the large repeat regions, such as those found in AtlA, is characteristic of surface proteins involved in ligand binding, and the peptidoglycan hydrolase domain may also mediate cell wall binding, possibly in a more complex manner.…”
Section: Discussionmentioning
confidence: 99%